Disturbances in Heaven. Made in China Yearbook 2016 - Franceschini, Ivan; Lin, Kevin; Loubere, Nicholas (ANU Press, 2017)
Labour and civil society are two fundamental components of international discussions concerning China today. Whether it is the arrest of labour activists or rights lawyers, the adoption of new industrial policies, or the passing of draconian rules on non-governmental organisations, the events occurring in these areas in China often make global headlines. At the same time, in spite of the grave challenges for workers and activists, the Chinese labour movement is witnessing significant developments, with the occurrence of some of the largest strikes in decades. All of this calls for more serious analysis from both scholars and practitioners, as well for critical engagement with a broader global audience interested in forging international solidarity. It is with these aims in mind that we have compiled this Made in China Yearbook 2016: Disturbances in Heaven, a collection of original articles by both scholars and activists, analysing the most important trends in Chinese labour and civil society over the past year. With its unique blend of in-depth scholarly work written in a direct, accessible style, this volume will allow readers to situate events and policies related to Chinese labour and civil society in a wider context, and serve as an indispensable reference book for international activists, practitioners, and policy-makers.